ОБГРУНТУВАННЯ МЕХАНІЗМУ ОРГАНІЗАЦІЇ АУТСОРСИНГОВИХ ПОСЛУГ НА ГАЗОТРАНСПОРТНИХ ПІДПРИЄМСТВАХ - Федорович, І. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article analyzes the main scientific approaches to the definition of the concept of "outsourcing", considers its essence as a tool for improving the efficiency of the enterprise and increasing its competitiveness in the market, identifies its main advantages and disadvantages, discloses the main principles of the formation of an effective mechanism for outsourcing auxiliary processes of gas transport companies. The outsourcing functions are investigated and its place in ensuring the sustainable development of the gas transportation company in the conditions of uncertainty, risks and competition intensification is determined. The theoretical principles of application of outsourcing at the enterprise are analyzed in order to reduce production costs, improve the quality and increase the competitiveness of products. The main factors determining the necessity of making a decision on outsourcing are established. The approach to it as an economic phenomenon is proposed, the classification of its types according to the economic content and the method of organization of interaction between enterprises is proposed. The mechanism of organization of outsourcing services in gas transport enterprises is defined, which should include the following stages: structuring of the main and auxiliary functions and processes, revealing of the key competencies, outsourcing market analysis, qualitative justification of outsourcing of individual processes, expert judgment on the use of outsourcing; choice of the organization's form with the outsourcer (open, closed outsourcing) taking into account strategic interests and opportunities of the enterprise; evaluating outsourcing proposals, requesting information from potential service providers, selecting an outsourcing partner. The basis for building a mechanism for organizing such services is the principles of outsourcing, which can be attributed to the following: integrity, flexibility, controllability, informational, efficiency, innovation, consistency, timeliness, openness, planning. The proposed principles of construction of the mechanism of outsourcing organization are the prerequisites for its development and play an important role in the further effectiveness of the functioning of the developed mechanism. The results of the evaluation confirmed the need to use the outsourcing strategy at gas transport companies.